2022
DOI: 10.1093/ehjci/jeac101
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial adiposity is independently linked to adverse cardiovascular phenotypes: a CMR study of 42 598 UK Biobank participants

Abstract: Aims We evaluated independent associations of cardiovascular magnetic resonance (CMR)-measured pericardial adipose tissue (PAT) with cardiovascular structure and function and considered underlying mechanism in 42 598 UK Biobank participants. Methods and results We extracted PAT and selected CMR metrics using automated pipelines. We estimated associations of PAT with each CMR metric using linear regression adjusting for age, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…We then fine-tuned a deep-learning model based on ResNet50 to annotate EPAT in the remaining participants. In a heldout test set of 50 individuals, the model achieved a Dice score of 0.80 compared with a human annotator, similar to a recently reported model based on UKB CMR data . We further excluded 788 participants whose 4-chamber images were not predicted to show at least 5 cm 2 of each cardiac chamber as a quality control step to remove misaligned or poor-quality images (eMethods and eFigure 1 in Supplement 1).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…We then fine-tuned a deep-learning model based on ResNet50 to annotate EPAT in the remaining participants. In a heldout test set of 50 individuals, the model achieved a Dice score of 0.80 compared with a human annotator, similar to a recently reported model based on UKB CMR data . We further excluded 788 participants whose 4-chamber images were not predicted to show at least 5 cm 2 of each cardiac chamber as a quality control step to remove misaligned or poor-quality images (eMethods and eFigure 1 in Supplement 1).…”
Section: Resultsmentioning
confidence: 57%
“…Paracrine or vasocrine release of cytokines and immune response factors from EAT to coronary arteries has been suggested to drive the development of atherosclerosis . However, EPAT and VAT have comparable associations with cardiovascular risk factors and the metabolic syndrome, which raises the question of whether many of the observed disease associations may reflect global consequences of unhealthy visceral adiposity rather than more localized cardiac effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 However, studies linked pericardial adiposity to adverse cardiovascular outcomes were independent from lipid profile. 42 Moreover, in a randomized clinical trial, weight loss interventions were associated with reduction in pericardial adipose tissue and improvement in lipid profile. 43 The study added to the literature by supporting the already existing clinical evidence that pericardial fat had a role in cardiovascular diseases independent of BMI 44 has traditionally been the most commonly used and simplest reproducible tool for measuring obesity and overall body adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had demonstrated a significant correlation between pericardial fat and increased total cholesterol, triglyceride and low‐density lipoprotein 41 . However, studies linked pericardial adiposity to adverse cardiovascular outcomes were independent from lipid profile 42 . Moreover, in a randomized clinical trial, weight loss interventions were associated with reduction in pericardial adipose tissue and improvement in lipid profile 43 …”
Section: Discussionmentioning
confidence: 99%